2021
DOI: 10.1177/0300060521999527
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone activates the cyclic AMP-protein kinase A signalling pathway by upregulating ABHD2 in fertile men

Abstract: Objective This was a prospective study to investigate whether progesterone affects sperm activity by regulating the cyclic AMP-protein kinase A (cAMP-PKA) signalling pathway via α/β hydrolase domain-containing protein 2 (ABHD2). Methods Spermatozoa were collected from healthy and infertile men (with oligoasthenospermia or abnormal acrosome; n = 30/group). The expression of and mutations in ABHD2 were detected by quantitative PCR, western blot, and gene sequencing. The expression of ABHD2 in the presence of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…C11orf74 enhances sperm motility and improves fertilization ( Majkowski et al, 2018 ). Progesterone can upregulate ABHD2 to activate the camp-PKA signaling pathway ( Jiang et al, 2021 ). These genes were strongly selected, suggesting that perennial estrus may result from a combination of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…C11orf74 enhances sperm motility and improves fertilization ( Majkowski et al, 2018 ). Progesterone can upregulate ABHD2 to activate the camp-PKA signaling pathway ( Jiang et al, 2021 ). These genes were strongly selected, suggesting that perennial estrus may result from a combination of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous cannabinoids inhibit the CatSper channel, and progesterone hydrolyzes the inhibitory cannabinoids by binding and activating the highly expressed type II domain dehydrogenase ABHD2 receptor on human spermatozoa [11,16,33]. Progesterone increased mRNA and protein levels of ABHD2 in healthy spermatozoa [34]. Previous studies revealed that the role of calcium channels in the sperm progesterone-mediated motility, using calcium channel blockers such as mibefradil, could not completely prevent the progesterone effects.…”
Section: Andrologiamentioning
confidence: 98%